Construction of pY-Af Vector for Expression of Thermostable Î±-L-Arabinofuranosidase in Saccharomyces cerevisiae - Wirajana, I Nengah; Puspaningsih, Ni Nyoman Tri; Wasito, Eddy Bagus; Kusuma, Soekry Erfan; Kimura, Tetsuya; Sakka, Kazuo (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
In this research,Â constructionÂ of expressionÂ vectorÂ for thermostable Î± -L-arabinofuranosidaseÂ in Saccharomyces cerevisiae was conducted. BJ1824 was conducted TheÂ Escherichia coli/S. cerevisiaeÂ shuttle vector, pYES2 wasÂ usedÂ asÂ parentalÂ vectorÂ inÂ construction.Â TheÂ abfAÂ geneÂ encodingÂ Î±-L- arabinofuranosidaseÂ from GeobacillusÂ thermoleovoransÂ IT-08Â wasÂ amplifiedÂ byÂ PCR,Â inÂ whichÂ theÂ plasmidÂ pTP510 wasÂ usedÂ asÂ a template. The amplification product was treated withÂ SacI and XhoI and then subcloned to the pYES2 vector, which was previously digested withÂ SacI andÂ XhoI. The recombinant plasmid was designated as pY-Af and propagatedÂ firstÂ inÂ E.Â coliÂ Top 10,Â andÂ thenÂ transformedÂ intoÂ S.Â cerevisiaeÂ BJ1824.Â ForÂ Î±- Larabinofuranosidase (AbfA) production, the yeast transformants were grown in YNBG selective medium and YPG rich medium, using galactose as an inducer. The AbfA activity was assayed by measuring the amount of p-nitrophenol (pNP) releasedÂ fromÂ p-nitrophenyl-Î±-L-arabinofuranosideÂ (pNPA) substrate at pH 6.0 and 70 ï°CÂ forÂ 30Â min.Â TheÂ recombinantÂ AbfAÂ activityÂ wasÂ detectedÂ inÂ eitherÂ ofÂ cultureÂ mediumÂ (0.98%),Â cellassociated (14.17%) and intracellular (84.85%) when recombinant yeast was grown in YPG rich medium.Key words:Â Î±-L-arabinofuranosidase; Saccharomyces cerevisiae; expression vector